HUELLA HÍDRICA DE UNA FINCA GANADERA LECHERA BAJO LAS CONDICIONES AGROECOLÓGICAS DEL VALLE DEL CAUCA - CARLOS AUGUSTO MARTÍNEZ MAMIAN; XIMENA ANDREA RUIZ ERAZO; SANDRA MORALES VELASCO (Biotecnología en el Sector Agropecuario y Agroindustrial, 2016)
The high water demands for agricultural production, has generated the need to quantify the consumption of this resource in order to establish management measures. Therefore a study was conducted to determine the water footprint of a dairy herd under the ecological conditions of the village of Rozo Municipality of Palmira Valle del Cauca. For the assessment took into account the methodology Chapagain, who sets the parameters for measuring the water green , blue and gray. A survey was applied to obtain the production data of the farm. The results showed that to produce one liter of milk 1,9 m3 of water, of which 97,4% are required per crop (fodder) for its production cycle is needed, the above demonstrates the need for alternatives to use and reuse of water within the livestock system.